The genetic background of Parkinson's disease and novel therapeutic targets - Salamon András (EXPERT OPINION ON THERAPEUTIC TARGETS, 2022)
Parkinson's disease (PD) is the second most common neurodegenerative disease worldwide. The median age of disease onset is around 60 years. From a genetic point of view, PD is basically considered a sporadic, idiopathic disease, however, hereditary components can be detected in 5-10% of patients. Expanding data are available regarding the targeted molecular therapy of the disease.The aim of this current review article is to provide brief clinical and molecular insight into three important genetic forms (LRRK2, SNCA, GBA) of hereditary PD subtypes and to present the human clinical trials in relation to these forms of the disease.These small hereditary subgroups are crucially important in drug development, because the general trend is that clinical trials that treat PD patients as a large group, without any separation, do not meet expectations. As a result, no long term conclusions can currently be drawn regarding the effectiveness of the molecules tested in these phase 1 and 2 studies. Further precise studies are needed in the near future.